2005
DOI: 10.1167/iovs.04-1224
|View full text |Cite
|
Sign up to set email alerts
|

Nonlethal Oxidant Injury to Human Retinal Pigment Epithelium Cells Causes Cell Membrane Blebbing but Decreased MMP-2 Activity

Abstract: Sustained or transient oxidant injury causes increased cell membrane blebbing but decreased activation of MMP-2. The findings lead to the hypothesis that blebs released in the absence of active MMP-2 may become trapped between the RPE and its basal lamina as sub-RPE deposits, possibly contributing to drusen formation in age-related macular degeneration. Also, the results lead to the postulation that oxidant injury disrupts the cell-specific surface proteases necessary to cleave and activate pro-MMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…20 We previously found that exposure to cigarette smoke and HQ resulted in RPE membrane blebbing and sub-RPE deposits in mice. 21,22 We also demonstrated that nonlethal HQ-induced oxidative injury in cultured RPE cells results in reorganization of actin cytoskeleton and blebs formation [22][23][24][25] relevant to the accumulation of deposits. Blebbing of the plasma membrane is an early morphological sign of cell injury, which occurs immediately after exposure to a wide variety of toxic agents.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…20 We previously found that exposure to cigarette smoke and HQ resulted in RPE membrane blebbing and sub-RPE deposits in mice. 21,22 We also demonstrated that nonlethal HQ-induced oxidative injury in cultured RPE cells results in reorganization of actin cytoskeleton and blebs formation [22][23][24][25] relevant to the accumulation of deposits. Blebbing of the plasma membrane is an early morphological sign of cell injury, which occurs immediately after exposure to a wide variety of toxic agents.…”
mentioning
confidence: 66%
“…24 GFP-ARPE-19 cells were pretreated for 1 hour with or without 20 mol/L of SB203580 or 60 nmol/L of okadaic acid, and then exposed to 100 mol/L of HQ for 6 hours. Figure 6, A and B, shows the extensive blebbing that occurs in GFP-ARPE-19 cells after exposure to nonlethal concentrations of HQ for 6 hours.…”
Section: Inhibition Of Hsp27 Phosphorylation Decreases Hq-induced Blementioning
confidence: 99%
“…Supporting the original reason why the eyecups were used to keep the RPE monolayer, the ARPE-19 cells grown to an established monolayer were able to suppress the activation of the phagolysosome in the phagocytizing macrophages. Other studies have grown the ARPE-19 cells to form an established monolayer before being assayed [8]. It demonstrates that as an intact monolayer the ARPE-19 cell line is very useful in understanding the role of human RPE produced factors in modulating immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are many reports showing almost the same activity of ARPE-19 cell monolayers to cultured primary RPE [8][9][10][11], the conditioned media of cultured ARPE-19 cells were assayed to see whether they suppress phagolysosome activation in phagocytizing macrophages. The ARPE-19 cells were cultured to confluence, or kept subconfluent before changing the media to the serum-free media for an additional 24 hours of incubation.…”
Section: The Effects Of Cultured Arpe-19 Cells On Macrophage Phagolysmentioning
confidence: 99%
See 1 more Smart Citation